Спорные вопросы приобретения права собственности на клад - Bystrowa, Maria (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an evaluation of the acquisition of the ownership of the treasure in the civil law of the Russian Federation. The author presenting the selected controversial issues according to the acquisition of the ownership of the treasure focus on its practical dimension with a special emphasis on the cultural heritage.